Opportunities And Challenges For Shopee Users In MSMEs - Gusti Erli Anggi Lubis; Siti Hawa Hasibuan; Angga Lesmana; Nurbaiti Nurbaiti (International Journal of Management Research and Economics, 2024)
The era of digitalization now has penetrate to various field life man . Phenomenon This bring impact significant to shift pattern buy and consume society , p This change method think as well as culture something community . Transformation This cause shift from approach conventional in nature physique going to a more digital approach and not tangible . Research methods used _ in study This namely the Qualitative Method with do data collection via Internet Searching. Many related articles , journals and ebooks _ with topic study . Rating result literacy depend on _ collected findings _ from various source , like books , journals , and reports before that , of course related with subject study . The existence of the Shopee application makes A convenience for MSME players to _ operate his business , that is impact Because wheel economy a country still Can turn with the existence of MSME actors and also sectors the become savior in the middle difficult conditions . _ Lots of it features provided _ like Shopee food, features the there is various type attractive offer _ consumer interest _ like Lots discount , free fare Send become A things that consumers find interesting so consumers _ sometimes more choose buy food via Shopee Food compared buy direct in place.